Metode DBSCAN dalam Pengelompokan Provinsi di Indonesia Berdasarkan Rasio Tenaga Kesehatan dan Tenaga Medis pada Tahun 2023 - Maharani, Listia; Martha, Zamahsary; Permana, Dony; Zilrahmi (Departemen Statistika Universitas Negeri Padang, 2025)
Health is a fundamental right of every citizen. This right is realized in the form of health services. Good health services have an adequate ratio of health and medical personnel. However, in reality, there are still many provinces that have a shortage of health and medical personnel. Therefore, clustering is carried out to make it easier for the government to group provinces that have similarities in terms of the ratio of health and medical personnel in Indonesia in 2023. Density Based Spatial Clustering of Applications with Noise (DBSCAN) is one of the clustering methods used. Using the DBSCAN method, two clusters were obtained with a silhouette coefficient value of 0.49. Cluster 0 is called noise because the observation points in group 0 are outliers. Cluster 0 consists of provinces with a higher ratio of healthcare and medical personnel than cluster 1.